Design solutions to improve resilience of metro vehicle to blast events. (December 2018) - El Koursi, El Miloudi; Bruyelle, Jean-Luc; Seddon, Richard; O'Neill, Conor
Highlights: We studied improvements in the design of metro vehicles for resilience to blast. We developed low-cost design solutions to promote their use in rolling stock. We designed measurement methodologies suitable for explosion inside a carriage. We conducted a full scale validation test. Abstract: Considerable effort is being devoted by researchers and stakeholders in order to improve the safety of metro systems with regard to terrorist attacks. The issue has been addressed by many researchers, taking into account the bow-tie model of safety management, in which the node is the terrorist attack, with on one side the causes of the attack (e.g. political issues, technical weaknesses) and on the other side the consequences (e.g. human, organisational, economical). The common goal is to implement a line of defence to isolate these causes and consequences, in order to prevent the attack from occurring and, should it happen, to mitigate its consequences as much as possible. This work takes into account the identified common attack methodologies and the behaviour of the surviving passengers in order to improve the situation management, assist the evacuation of and rescue to survivors. Moreover, technological improvements to the structure and critical systems of the vehicle have been devised and tested in real situation. This paper focuses particularly on the behaviour of people in blast situation, and presents the conclusions of the project on these effects and the related improvements of the vehicles design in order to improve resilience and survivability to blast.